Model handlu światowego w 1970 roku - Mennes, Loet B.M. (Wydział Prawa i Administracji UAM, 1968)
This world trade model examines trade flows in 1970 between six country groups and seven groups of goods and services comprising together the whole world trade in goods and services. Using as division criteria: per capita income, the political regime, the commodity composition of exports and the location of the country on the globe — the following country groups have been distinguished: 1. U.S.A., 2. Industrial Europe, 3 Semi-industrialized countries, 4. Non-industrialized countries, 5. Oil countries, 6. Socialist countries. Within each of the country groups seven sectors have been taken into account, namely: Food, Raw materials, Oils, Chemicals, Equipment, other manafacturers and services. The sum of their products gives the gross domestic product at factor costs of the country group concerned. For each of the first five country groups linearized growth models of the Harrod-Domar type have been drawn up. A condensed version of the models used for the country groups mentioned is one sector model which consists of six equations and nine variables. The purpose of the model is to give a comparative static analysis of the consequences of giving aid to the less developed countries. For each country group a model has been built as an extension of the condensed model, in the sense that seven sectors instead of one have been taken into account. In turn, the country group models have been linked into a world model by means of definitions of the volumes of world trade. Thus for each country group a definition of world trade of this commodity, as the sum of the imports of the individual groups has been added. Moreover, a definition of world price had to be added which defines it as a weighed average of the individual domestic prices. The author attempts to make some statements from the individual country group models. In each, a model giving aid, a new equilibrium situation arises where the G.D+P, of the giving country is smaller than in the original equilibrium situation. For a country receiving aid the opposite reasoning holds. Furthermore, giving aid means a decrease of a. country's domestic price level, a decrease of its imports and an increase of exports. A detailed survey of the results of the world model can be found in appendix C. Four combinations of giving and receiving aid have been dealt with.
A World Trade Model for 1970